Slovenski gostinci in pomen slovenskih gostiln v Zagrebu v 30-ih letih 20. stoletja - Kržišnik-Bukić, Vera (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 1993)
In the period between the two world wars Slovenians represented at least one tenth of the whole population in Zagreb. An important role was played by Slovenian innkeepers. They owned a number of inns, restaurants, coffee houses, pubs, canteens and even a hotel. All these inns recommended their services especially to Slovenian guests. In many cases they offered them room for social gatherings and other activities. The Slovene inns therefore turned into places of meeting of the Zagreb Slovenians, where Slovene spirit strengthened itself.
Keywords: 20.st.; gostilne; gostinstvo; narodna identiteta; narodna zavest; Slovenci; slovenski izseljenci; Zagreb